ASSESSING FOOD VENDORS KNOWLEDGE AND PERCEPTION OF MEDICAL SCREENING ON HYGIENE PRACTICES IN ASSIN FOSU TOWNSHIP - Opare, Gloria; Opoku, Oscar Agyemang; Annan, Eunice Akua (International Journal of Health Concord, 2026)
The study was to examine food vendors’ knowledge and perception in medical screening on hygiene practices in the Assin Fosu Township. The study employed descriptive cross-sectional design of the quantitative approach. The study sampled 422 food vendors in Assin Fosu Township. The study employed questionnaire and was analysed using frequencies, percentages, means and standard deviations with the aid of Statistical Package for Service Solution. In addition, linear regression was used to determine the relationship between knowledge on medical screening on hygiene practices and perception on medical screening. Food vendors were moderately knowledgeable on hygienic practices. Food vendors have good perception about medical screening. However, there were concerns about the cost and time consumption associated with medical screening. There was a positive correlation between knowledge about medical screening and both hygienic and medical screening practices. While the relationship between knowledge and practices was significant, it was observed to be weak for hygiene practices but moderate for medical screening practices. Increased knowledge about medical screening positively influenced both hygiene and medical screening practices among respondents. The District Environmental Health Office has to develop comprehensive education and training programs focusing on proper hygiene practices for food vendors. Also, the Assin Fosu Municipal Assembly should address concerns regarding the cost and time consumption associated with medical screening. Moreover, the Assin Fosu Municipal Assembly should implement awareness campaigns to highlight the benefits of medical screening in maintaining higher hygiene standards and improving food safety.